Edukasi dan Pelatihan Diversifikasi Produk Perikanan Tingkatkan Nilai Tambah KUD Mina Asri Juntinyuat - Sumarta Sumarta; Kusyana Kusyana; Tenda Budiyanto; Zamzami Zamzami (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program, a 30-day Internship (PKL), focused on educating and training members of KUD Mina Asri Junti in fisheries product diversification to enhance added value. The program involved needs assessment, module development covering processing techniques (frozen fillet, dried products, ready-to-eat), food safety, packaging, and basic marketing. Participatory training methods, including demonstrations and hands-on practice, were employed. Evaluation showed increased knowledge and skills among participants and the emergence of product diversification initiatives. However, challenges like limited capital and the need for ongoing support were identified. The program successfully initiated a positive change, laying the groundwork for sustainable fisheries product diversification in the community.